Interactions in protein solutions close to liquid–liquid phase separation: ethanol reduces attractions via changes of the dielectric solution properties. Issue 39 (5th October 2021) - Hansen, Jan; Uthayakumar, Rajeevann; Pedersen, Jan Skov; Egelhaaf, Stefan U.; Platten, Florian
Abstract : Adding a moderate amount of ethanol to a protein solution weakens the net inter-protein attraction and thus changes the LLPS binodal and the SAXS intensity. The effect can be entirely accounted for by considering the dielectric solution properties. Abstract : Ethanol is a common protein crystallization agent, precipitant, and denaturant, but also alters the dielectric properties of solutions. While ethanol-induced unfolding is largely ascribed to its hydrophobic parts, its effect on protein phase separation and inter-protein interactions remains poorly understood. Here, the effects of ethanol and NaCl on the phase behavior and interactions of protein solutions are studied in terms of the metastable liquid–liquid phase separation (LLPS) and the second virial coefficient B 2 using lysozyme solutions. Determination of the phase diagrams shows that the cloud-point temperatures are reduced and raised by the addition of ethanol and salt, respectively. The observed trends can be explained using the extended law of corresponding states as changes of B 2 . The results for B 2 agree quantitatively with those of static light scattering and small-angle X-ray scattering experiments. Furthermore, B 2 values calculated based on inter-protein interactions described by the Derjaguin-Landau-Verwey-Overbeek (DLVO) potential and considering the dielectric solution properties and electrostatic screening due to the ethanol and salt content quantitatively agree with the experimentally observed B 2 values.